2005
DOI: 10.1128/jb.187.16.5552-5559.2005
|View full text |Cite
|
Sign up to set email alerts
|

Methanol-Dependent Gene Expression Demonstrates that Methyl-Coenzyme M Reductase Is Essential in Methanosarcina acetivorans C2A and Allows Isolation of Mutants with Defects in Regulation of the Methanol Utilization Pathway

Abstract: Methanosarcina acetivorans C2A is able to convert several substrates to methane via at least four distinct methanogenic pathways. A common step in each of these pathways is the reduction of methyl-coenzyme M (CoM) to methane catalyzed by methyl-CoM reductase (MCR). Because this enzyme is used in each of the known pathways, the mcrBDCGA operon, which encodes MCR, is expected to be essential. To validate this prediction, a system for conditional gene inactivation was developed. A heterologous copy of the mcrBDCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…To obtain a clearer picture of the phylogenetic distribution of SepRS͞ SepCysS and the methanogenesis genes, directed environmental sequencing efforts are called for, and genetic experiments in Methanosarcina acetivorans, e.g., ref. 51, which contains both the archaeal and bacterial routes for cysteine coding and biosynthesis, will help in understanding why this organism has retained the archaeal pathway and shed light on the reason for the apparent functional redundancy. Directed by hypotheses generated from the evolutionary data, such work will lead to a deeper understanding of these archaea and the connection between information processing and metabolism in cellular evolution.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain a clearer picture of the phylogenetic distribution of SepRS͞ SepCysS and the methanogenesis genes, directed environmental sequencing efforts are called for, and genetic experiments in Methanosarcina acetivorans, e.g., ref. 51, which contains both the archaeal and bacterial routes for cysteine coding and biosynthesis, will help in understanding why this organism has retained the archaeal pathway and shed light on the reason for the apparent functional redundancy. Directed by hypotheses generated from the evolutionary data, such work will lead to a deeper understanding of these archaea and the connection between information processing and metabolism in cellular evolution.…”
Section: Resultsmentioning
confidence: 99%
“…The uidA gene of E. coli encodes the easily assayable enzyme ␤-glucuronidase, which has previously been used as a reporter gene in Methanosarcina and other methanoarchaea (2,12,23). We constructed uidA reporter gene fusions to the promoter regions of the mtaCB1 (23), mtaCB2, and mtaCB3 operons.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, the level of regulation measured in our mtaCB1 and mtaCB2 fusions is unprecedented in the archaeal domain. We have recently shown that it is possible to select constitutive mutants by fusing the mtaC1 promoter to an essential gene (23), suggesting that genetic approaches should be fruitful in unraveling this mystery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were not pre-adapted for b-glucuronidase activity measurements on DMS in order to minimize handling of this highly toxic (to humans) chemical. The preparation of cell extracts and b-glucuronidase assay method were as previously described (Rother et al, 2005), using a Varian Cary 50 UV-Vis spectrophotometer equipped with an 18 multicell holder was used for all assays.…”
Section: Extract Preparation and B-glucuronidase Assaymentioning
confidence: 99%